Genetic control of the tree-ring response of Douglas-fir (Pseudotsuga menziesii (Mirb.) Franco) to the 2003 drought and heat-wave in France - Martinez Meier, Alejandro; Sanchez, Leopoldo; Dalla Salda, Guillermina; Pastorino, Mario Juan; Gautry, Jean-Yves; Gallo, Leonardo Ariel; Rozenberg, Philippe (Springer, 2020)
The genetic control of tree ring growth in Douglas-fir in response to the drought and heat-wave that occurred in 2003 in Europe was studied with microdensity profiles in three clonal experiments located in three different French regions. The drought and heat-wave significantly affected Douglas-fir wood formation. The Chassenoix site (Northeast of Massif-Central) was more severely affected that the other two: the 2003 year-ring was narrower and less dense than in the other sites and than the previous (2002) and following (2004) year-rings in the same site: ring growth stopped earlier and latewood did not develop completely. The year-rings 2004 and 2002 were very similar in this site. There was a significant genetic control for all ring parameters in the three sites and during the three years. The heritability was highly variable between years and among sites, without any clear pattern in this variability, except in Chassenoix where it was slightly lower in the 2003 year-ring. Variables measuring the response of trees to the 2003 event, i.e., the difference in ring width between 2002 and 2003, or between 2003 and 2004, showed a very variable degree of genetic control, from very low to relatively high. Douglas-fir seemed plastic enough to acclimate to the drought and heat-wave and then to recover during 2004. Furthermore the level of heritability estimated demonstrates that Douglas-fir has an adaptive potential that could be useful for multi-generation long-term response.